Aromatic poly-1, 3, 4-oxadiazole membrane material and preparation method thereof
By introducing flexible structural units into POD materials and synthesizing new POD film materials, the problem of brittle fracture of POD materials during graphitization is solved, and the flexibility of the material is improved and the thermal conductivity optimization is achieved. It is suitable for applications that require bending. Scene.
Patent Information
- Application Number
- CN202411676052.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing POD materials are brittlely fractured during graphitization, resulting in poor membrane flexibility and cannot be suitable for application scenarios where bending is required, and the traditional composite material route cannot effectively solve this problem.
By introducing flexible structural units, functionalized phthalic acid is synthesized by dehydration using amino-substituted phthalic acid and substituted succinic anhydride, and synthesized on the polymerization production line with comonomers to prepare a new POD film material.
It significantly improves the flexibility of the POD film material, keeping it intact and not fragmented during the high-temperature graphitization process, and can be carbonized and graphitized through the rolling process, reducing the cost of heat treatment. The resulting graphitized material has excellent thermal conductivity and Bending resistance.
Smart Images

Figure BDA0005147075260000021 
Figure BDA0005147075260000031 
Figure BDA0005147075260000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an aromatic poly-1,3,4-oxadiazole film material and a preparation method thereof. Background Art
[0002] Aromatic poly-1,3,4-oxadiazole (POD for short) material is a special engineering plastic whose main chain is composed of aromatic heterocyclic oxadiazole. Due to its tightly stacked rigid skeleton, its molecular structure has excellent heat resistance, flame retardancy, electrical insulation and mechanical strength, etc. It has broad application prospects in many fields including aerospace, electronic appliances, high-performance fibers, etc. Artificial thermal conductive graphite film made by carbonization and graphitization of POD film material has the advantages of low cost, regular crystal structure, higher thermal conductivity and small expansion coefficient, and has gradually become a research hotspot in recent years. Under high temperature, the molecular structure of POD is rearranged and transformed, gradually changing to an orderly arranged graphite structure, and finally forming a layered structure similar to graphite. The resulting graphitized material has important applications in thermal conductive materials, electrode materials, high temperature resistant structural materials and other fields.
[0003] However, during the graphitization process, the rigidity of POD materials will bring a series of adverse effects. Due to its high hardness and brittleness, stress concentration is easily generated during the high-temperature graphitization process, causing cracks or even breakage in the material. Further, the material is difficult to carbonize through the coil firing process. Currently, only the sheet firing process can be used. The graphitization cost is high, and the resulting graphite film has poor flexibility and cannot be used in application scenarios that require bending. This will not only affect the appearance quality of the material, but also reduce the performance and service life of the material, increase the firing cost, and greatly limit its scope of application. Therefore, it is of great significance to research and develop some new flexible POD materials to improve the rigidity of the material and meet actual needs.
[0004] In order to obtain better flexibility, compounding POD materials with other flexible materials is a commonly used modification method. For example, the Chinese patent document "A braided fabric woven from polyoxadiazole filaments and quartz fiber yarns" (Publication No. CN206279302U) discloses that the braided fabric is formed by interweaving warp and weft to form a grid. The braided fabric mixes polyoxadiazole filaments and quartz fibers together and then weaves them into a braided fabric. It has high heat resistance and can increase its flexibility and is not easy to break. Compounding POD with other flexible materials can improve the overall flexibility of the material, but this method cannot be used as a graphitization raw material, and cannot avoid the brittle fracture of the POD material itself during the graphitization process. The material still has problems such as being unable to be rolled and burned and the graphite film being not resistant to bending.
[0005] Given that the development of flexible POD materials is currently difficult and the traditional composite material route cannot help solve the problems existing in the graphitization process, it is necessary to develop a new type of POD material based on chemical molecular design and by introducing flexible structural units. Summary of the invention
[0006] In order to solve the problem of poor film flexibility caused by brittle fracture during graphitization of existing POD materials, the present invention proposes an aromatic poly-1,3,4-oxadiazole film material.
[0007] The technical solution of the present invention is as follows:
[0008] An aromatic poly-1,3,4-oxadiazole membrane material, the structural formula of which is as follows:
[0009]
[0010] Among them, x:y:z=(0.40~1):(0~0.30):(0~0.30), and y and z are not 0 at the same time.
[0011] The present invention also provides a method for preparing the above aromatic poly-1,3,4-oxadiazole film material, comprising the following steps:
[0012] Functionalized phthalic acid is synthesized by dehydrating amino-substituted phthalic acid and substituted succinic anhydride;
[0013] The obtained functionalized phthalic acid, terephthalic acid and hydrazine salt are subjected to polycondensation reaction under the action of fuming sulfuric acid to prepare a POD solution;
[0014] The POD solution is vacuum degassed and filtered, and then extruded to a coagulation roller through a forming die head, and coagulated in a multi-stage coagulation bath to obtain a wet film layer. The obtained wet film is fully washed and then dried to obtain an aromatic poly-1,3,4-oxadiazole film material.
[0015] Preferably, the amino-substituted phthalic acid is 5-aminoisophthalic acid, 2-aminoterephthalic acid or a mixture of the two;
[0016] The optional structures of amino-substituted phthalic acid are listed below:
[0017]
[0018] The substituted succinic anhydride is one of butyl succinic anhydride, decyl succinic anhydride, dodecyl succinic anhydride, tetradecyl succinic anhydride, hexadecyl succinic anhydride, octadecyl succinic anhydride, allyl succinic anhydride, nonenyl succinic anhydride, and dodecenyl succinic anhydride, or a mixture of at least two of them.
[0019] The optional structures of substituted succinic anhydride are listed below:
[0020]
[0021]
[0022] Preferably, in the synthesis of the functionalized phthalic acid, the molar ratio of amino-substituted phthalic acid to substituted succinic anhydride is (0.80-1.30):1.
[0023] Preferably, the functionalized phthalic acid is functionalized isophthalic acid, functionalized terephthalic acid or a mixture thereof; the molar ratio of the functionalized isophthalic acid, functionalized terephthalic acid and terephthalic acid is (0-0.30):(0-0.30):(0.40-1);
[0024] The molar ratio of the hydrazine salt to the total amount of functionalized phthalic acid and terephthalic acid is (1.02-1.10):1.
[0025] Preferably, the mass fraction of SO3 in the oleum is 5% to 50%.
[0026] Preferably, the solid content of the reaction system of the polycondensation reaction is 4 to 20 wt.%.
[0027] Preferably, the reaction conditions are: stirring at 60-90° C. for 1-2 h, then heating to 100-120° C. and stirring for 1-3 h, then adding benzoic acid for end-capping, then heating to 130-150° C. and stirring for 0.5-2 h, and ending the reaction after the benzoic acid is dissolved and the end-capping is completed.
[0028] Preferably, the multi-stage coagulation bath is a three-stage coagulation bath, and the three-stage coagulation bath adopts dilute sulfuric acid solutions with different mass concentrations, the first stage mass concentration is 35-55wt.%, the second stage mass concentration is 20-30wt.%, and the third stage mass concentration is 5-15wt.%; the temperature of the multi-stage coagulation bath is 30-60°C.
[0029] Preferably, the drying process is: first drying at 90-130°C, and then heat setting at 200-250°C.
[0030] Compared with the prior art, the specific beneficial effects of the present invention are:
[0031] 1. The POD membrane material provided by the present invention utilizes cheap and readily available amino-substituted phthalic acid and substituted succinic anhydride to synthesize functionalized phthalic acid through dehydration. The original POD material polymerization production line can be upgraded to synthesize a new POD material by auxiliary addition of comonomers without the need for additional equipment. By selecting raw materials with different substitution structures, the flexibility of the synthesized series of materials can be flexibly controlled.
[0032] 2. The process of the present invention significantly improves the flexibility of the final POD film material, and the material remains intact and does not break during the subsequent high-temperature graphitization process. The material can be further carbonized and graphitized through a roll-to-roll process (roll-to-roll firing). Compared with the current sheet-to-sheet firing process (sheet-to-sheet firing), the heat treatment cost is greatly reduced, and its comprehensive cost does not exceed 60% of mainstream heat dissipation materials such as graphene films and PI films.
[0033] 3. The graphitized material made from the material of the present invention has both the excellent thermal conductivity of the POD structure (thermal conductivity coefficient > 1700W / (m·K)) and good bending resistance (bending resistance (R1, 180 degrees) ≥ 100,000 times), breaking through the limitation that traditional POD graphite materials cannot be used in application scenarios that require bending.
[0034] The present invention has broad application prospects in the field of high thermal conductivity materials, and can be specifically applied to new products such as foldable screen mobile phones and square batteries. DETAILED DESCRIPTION
[0035] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as limiting the present invention.
[0036] Example 1.
[0037] (1) Preparation of POD solution: 5-aminoisophthalic acid and butyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 15.6 parts of butyl succinic anhydride and 189.7 parts of N, N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 16.8 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added for end-capping, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0038] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0039] Example 2.
[0040] (1) Preparation of POD solution: 2-aminoterephthalic acid and butyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 2-aminoterephthalic acid, 15.6 parts of butyl succinic anhydride and 189.7 parts of N, N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 16.8 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added for end-capping, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0041] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0042] Example 3.
[0043] (1) Preparation of POD solution: Using 5-aminoisophthalic acid or 2-aminoterephthalic acid and butyl succinic anhydride as raw materials, 18.1 parts of 5-aminoisophthalic acid or 2-aminoterephthalic acid, 15.6 parts of butyl succinic anhydride and 189.7 parts of N,N-dimethylformamide were mixed by weight, heated under reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate was washed with water and dried to obtain the corresponding functionalized isophthalic acid or functionalized terephthalic acid.
[0044] In a polymerization kettle, add 77.8 parts of terephthalic acid, 8.4 parts of functionalized isophthalic acid, 8.4 parts of functionalized terephthalic acid, and 71.3 parts of hydrazine sulfate, and then add 20% fuming sulfuric acid to a solid content of 10% and mix well, heat to 85°C and stir for 2 hours, then continue to heat to 120°C and stir for 3 hours, add 2.1 parts of benzoic acid to cap, and then heat to 140°C and stir for 2 hours to obtain a POD solution.
[0045] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0046] Example 4.
[0047] (1) Preparation of POD solution: 5-aminoisophthalic acid and decylsuccinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 24 parts of decylsuccinic anhydride and 189.7 parts of N,N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 21.2 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added to cap, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0048] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0049] Example 5.
[0050] (1) Preparation of POD solution: 5-aminoisophthalic acid and dodecyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 26.8 parts of dodecyl succinic anhydride and 189.7 parts of N,N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 22.7 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added to cap, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0051] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0052] Example 6.
[0053] (1) Preparation of POD solution: 5-aminoisophthalic acid and tetradecyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 29.6 parts of tetradecyl succinic anhydride and 189.7 parts of N,N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 24.2 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added to cap, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0054] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0055] Example 7.
[0056] (1) Preparation of POD solution: 5-aminoisophthalic acid and hexadecyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 32.5 parts of hexadecyl succinic anhydride and 189.7 parts of N,N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 25.7 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, then continued to heat to 120°C and stirred for 3 hours, 2.1 parts of benzoic acid are added for end-capping, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0057] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0058] Example 8.
[0059] (1) Preparation of POD solution: 5-aminoisophthalic acid and octadecyl succinic anhydride are used as raw materials. By weight, 18.1 parts of 5-aminoisophthalic acid, 35.3 parts of octadecyl succinic anhydride and 189.7 parts of N,N-dimethylformamide are mixed, heated to reflux for 12 hours, and poured into water to obtain a white precipitate. The precipitate is washed and dried to obtain the corresponding functionalized phthalic acid. In a polymerization reactor, 77.8 parts of terephthalic acid, 27.2 parts of functionalized phthalic acid, and 71.3 parts of hydrazine sulfate are added, and then 20% fuming sulfuric acid is added to a solid content of 10% and mixed evenly, heated to 85°C and stirred for 2 hours, and then continued to heat to 120°C and stirred for 3 hours, and 2.1 parts of benzoic acid are added to cap, and then heated to 140°C and stirred for 2 hours to obtain a POD solution.
[0060] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0061] Comparative Example 1.
[0062] (1) Preparation of POD solution: In a polymerization kettle, 86.4 parts of terephthalic acid and 71.3 parts of hydrazine sulfate were added by mass, and then 20% fuming sulfuric acid was added to a solid content of 10% and mixed evenly, the temperature was raised to 85°C and stirred for 2 h, and then the temperature was further raised to 120°C and stirred for 3 h, 2.1 parts of benzoic acid was added for end-capping, and then the temperature was raised to 140°C and stirred for 2 h to obtain a POD solution.
[0063] (2) Preparation of POD membrane material: The POD solution was vacuum degassed and filtered, extruded onto a coagulation roller through a forming die, and then coagulated in a three-stage coagulation bath (the first coagulation bath was a 40°C, 45wt.% dilute sulfuric acid solution, the second coagulation bath was a 45°C, 25wt.% dilute sulfuric acid solution, and the third coagulation bath was a 50°C, 10wt.% dilute sulfuric acid solution) to obtain a wet film layer. The wet film was fully washed and dried at 110°C, and then heat-set at 250°C to obtain a POD film. The film thickness was 120 μm, and the thickness after graphitization was 40 μm.
[0064] Comparative Example 1 adopts conventional monomer polymerization without introducing flexible structural units.
[0065] Effect example.
[0066] The physical properties of the POD films corresponding to Examples 1 to 8, Comparative Example 1 and commercially available samples and the properties of the prepared graphite films were tested, and the test results are shown in Table 1.
[0067] Table 1
[0068]
[0069] From the data in the above table, it can be seen that the POD material prepared by the present invention has a higher elongation at break and a lower fracture strength. Compared with the commercially available POD material, the material flexibility is significantly improved, and the flexibility of the synthesized series of new POD materials is flexible and adjustable. Therefore, the film-forming adaptation of the POD material prepared by the present invention to the coil-to-coil process has the important significance of meeting actual needs.
[0070] The graphitized material prepared by the material of the present invention has both the excellent thermal conductivity of the POD structure (thermal conductivity coefficient > 1700W / (m·K)) and good bending resistance (bending resistance (R1, 180 degrees) ≥ 100,000 times), breaking through the limitation that traditional POD graphite materials cannot be used in application scenarios that require bending, and can be applied to new products such as foldable screen mobile phones and square batteries.
[0071] In addition, the raw materials of the present invention are easily available, the synthesis is simple, the production efficiency is high, and the technology upgrade can be achieved by adding copolymer monomers to the original production line without the need for additional equipment investment. It has an outstanding cost advantage, and its comprehensive cost does not exceed 60% of mainstream heat dissipation materials such as graphene film and PI film, and has broad application prospects in the field of high thermal conductivity materials.
[0072] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. An aromatic poly-1,3,4-oxadiazole membrane material, characterized in that: The structural formula is as follows: Among them, x:y:z=(0.40~1):(0~0.30):(0~0.30), and y and z are not 0 at the same time.
2. A method for preparing an aromatic poly-1,3,4-oxadiazole film material as claimed in claim 1, characterized in that: The steps include: Functionalized phthalic acid is synthesized by dehydrating amino-substituted phthalic acid and substituted succinic anhydride; The obtained functionalized phthalic acid, terephthalic acid and hydrazine salt are subjected to polycondensation reaction under the action of fuming sulfuric acid to prepare a POD solution; The POD solution is vacuum degassed and filtered, and then extruded to a coagulation roller through a forming die head, and coagulated in a multi-stage coagulation bath to obtain a wet film layer. The obtained wet film is fully washed and then dried to obtain an aromatic poly-1,3,4-oxadiazole film material.
3. The method for preparing the aromatic poly-1,3,4-oxadiazole membrane material according to claim 2, characterized in that: The amino-substituted phthalic acid is 5-aminoisophthalic acid, 2-aminoterephthalic acid or a mixture of the two; The substituted succinic anhydride is one of butyl succinic anhydride, decyl succinic anhydride, dodecyl succinic anhydride, tetradecyl succinic anhydride, hexadecyl succinic anhydride, octadecyl succinic anhydride, allyl succinic anhydride, nonenyl succinic anhydride, and dodecenyl succinic anhydride, or a mixture of at least two of them.
4. The method for preparing the aromatic poly-1,3,4-oxadiazole film material according to claim 2, characterized in that: The molar ratio of the amino-substituted phthalic acid to the substituted succinic anhydride is (0.80-1.30):
1.
5. The method for preparing the aromatic poly-1,3,4-oxadiazole membrane material according to claim 2, characterized in that: The functionalized phthalic acid is functionalized isophthalic acid, functionalized terephthalic acid or a mixture of the two; the molar ratio of the functionalized isophthalic acid, functionalized terephthalic acid and terephthalic acid is (0-0.30):(0-0.30):(0.40-1); The molar ratio of the hydrazine salt to the total amount of functionalized phthalic acid and terephthalic acid is (1.02-1.10):
1.
6. The method for preparing an aromatic poly-1,3,4-oxadiazole membrane material according to claim 2, characterized in that: The mass fraction of SO3 in the oleum is 5% to 50%.
7. The method for preparing an aromatic poly-1,3,4-oxadiazole film material according to claim 2, characterized in that: The solid content of the reaction system of the polycondensation reaction is 4 to 20 wt.%.
8. The method for preparing an aromatic poly-1,3,4-oxadiazole film material according to claim 2, characterized in that: The reaction conditions are: stirring at 60-90° C. for 1-2 h, then continuing to heat up to 100-120° C. and stirring for 1-3 h, then adding benzoic acid to cap the mixture, and then heating up to 130-150° C. and stirring for 0.5-2 h, and the reaction is terminated after the benzoic acid is dissolved and the capping is completed.
9. The method for preparing an aromatic poly-1,3,4-oxadiazole film material according to claim 2, characterized in that: The multi-stage coagulation bath is a three-stage coagulation bath, which uses dilute sulfuric acid solutions with different mass concentrations, with the first-stage mass concentration being 35-55wt.%, the second-stage mass concentration being 20-30wt.%, and the third-stage mass concentration being 5-15wt.%; the temperature of the multi-stage coagulation bath is 30-60°C.
10. The method for preparing an aromatic poly-1,3,4-oxadiazole membrane material according to claim 2, characterized in that: The drying process is as follows: firstly drying at 90-130°C, and then heat setting at 200-250°C.
Citation Information
Patent Citations
By gathering knitting that evil diazole long filament of virtue and quartz fiber yarn were made into
CN206279302U
Asymmetric bismaleimide containing 1, 3, 4-oxadiazole structure and preparation method thereof
CN102942564A
Preparation method of polyoxadiazole and aramid fiber based transparent film
CN117777505A
Production of oxadiazole derivative polymer
JP2000273171A
Cited By
POD precursor film, POD-based graphite film and preparation methods of POD precursor film and POD-based graphite film
CN119842231A